Cellular entry of white spot syndrome virus and antiviral immunity mediated by cellular receptors in crustaceans. Issue 93 (October 2019) - Zheng, Shu-cheng; Xu, Jiao-yang; Liu, Hai-peng
Abstract: Enveloped virus usually utilizes the receptor-mediated multiple endocytic routes to enter permissive host cells for successful infection. Cellular receptors are cell surface molecules, either by helping viral attachment to cell surface followed by internalization or by triggering antiviral immunity, participate in the viral-host interaction. White spot syndrome virus (WSSV), the most lethally viral pathogen with envelope and double strand DNA genome in crustacean farming, including shrimp and crayfish, has been recently found to recruit various endocytic routes for cellular entry into host cells. Meanwhile, other than the typical pattern recognition receptors for recognition of WSSV, more and more putative cellular receptors have lately been characterized to facilitate or inhibit WSSV entry. In this review, recent findings on the endocytosis-dependent WSSV entry, viral entry mediated by putative cellular receptors, the molecular interplay between WSSV and cellular receptors, and the following anti -WSSV immunity are summarized and discussed, which may provide us a better understanding of the WSSV pathogenesis and further possible antiviral control of white spot disease in crustacean farming. Highlights: Recent findings on the putative cellular receptors-mediated recognition and entry of WSSVare summarized. Advances in cellular receptors-mediated sensing of WSSV and triggering of anti -WSSV immunity are discussed. IgSF receptors, Integrin, Laminin receptor, Chitin-binding protein and glucose transporter 1 mediate WSSV entry. Toll-like receptors, C-type lectins and Scavenger receptors sense WSSV and trigger antiviral immunity.